Measurement, monitoring and knowledge of blood pressure: May Measurement Month, Colombia 2017 (2019)
To describe the findings of implementing May Measurement Month 2017 in the adult Colom-bian population to raise awareness of the importance of blood pressure measuring, monitoring,and awareness.